Dispute Resolution in Consumer Protection in the Financial Services Sector Perspective Sadd al-Zari’ah - Taufiq, Muhammad (UIN Siber Syekh Nurjati Cirebon, 2025)
The misuse of personal data by third parties on fintech lending platforms—without consent through a written statement—poses a serious threat to data security and consumer rights. This study aims to offer a conceptual framework for financial service providers and the public concerning the regulation of personal data usage. Employing the Sadd al-Zari’ah approach, this research highlights the importance of preventing actions that may lead to disputes in the financial services sector. The study adopts a normative legal research method with two approaches: the statutory approach and the conceptual approach. The primary legal reference is Financial Services Authority Regulation (POJK) Number 22 of 2023. Data were obtained through literature review and analyzed qualitatively using descriptive techniques. The findings show that consumer protection dispute resolution in the financial services sector can be pursued through both preventive and repressive efforts by applying the concept of Sadd al-Zari’ah. This approach aims to block potential harm at its root by closing avenues that may lead to legal violations or injustice.Keywords: Dispute Resolution; Financial Services Sector; Sadd al-Zari’ah; Consumer Protection